The Value of Patience in the Storybook “Biji Merah Luna” by Ammy Kudo - Barojah (Lembaga Kajian Nusantara Raya UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2024)
Gardening is an activity that can be done by various groups, ranging from youth, parents and even children. One of the media that the author wants to discuss in applying the character values of patience is through storybook media. One of the storybooks that describes planting trees in early childhood is the book “Luna's Red Seeds” by Ammy Kudo. The purpose of this study is to dissect the contents of the storybook “Biji Merah Luna” by Ammy Kudo where the book tells how the process of a child planting fruit seeds until finally the seeds grow. This research is a descriptive research using qualitative research design. Data analysis for this research uses content analysis techniques. Based on the results of the research, there is a finding of the value of patience in the storybook “Biji Merah Luna” by Ammy Kudo. The finding of the value of patience is aimed at the process of patience that Luna feels from the process of planting tree seeds until the pohin grows. In addition to the value of patience, there is also the value of environmental care that must be applied in early childhood. This value is shown from Luna's enthusiasm for the tree planting process.